Analisis Tanggung Jawab Negara dalam Perlindungan Anak Korban Konflik Sosial dari Perspektif Hukum Nasional - Salsabila, Nadine Rayna; Isharyanto, , (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
Children's human rights have become part of the human rights guaranteed in the 1945 Constitution of the Republic of Indonesia. in the 1945 Constitution of the Republic of Indonesia. State responsibility in the protection of child victims of social conflict in this study has the scope of policies, programs and activities issued and or implemented by the Ministry of Women's Empowerment and Child Protection (PPPA) as the state's representation in child protection Women's Empowerment and Child Protection (PPPA) as the representation of the state in child protection. The type of research conducted is empirical normative legal research that focuses on positive legal norms in the form of laws and regulations. The data collection method used is primary data obtained directly through interviews with selected informants, while secondary data is obtained from books, journals, the internet, and other reliable literature studies. The approach used by the author is the statute approach and case approach. The results show that the legislation in the field of in the field of child protection of victims of social conflict have regulated harmoniously harmoniously in accordance with the substance and order of the applicable legislation. applicable legislation. Implementation of child protection of victims of social conflict in Indonesia by the Ministry of PPPA has also been carried out well in accordance with its duties, functions and authorities. in accordance with its duties, functions, and authorities, although to be maximized it still needs more support and improvement. said to be maximized, further support and improvement is still needed. further support and improvement are still needed.